Male Androgenetic Alopecia : Response To Finasteride - Thakkar Suruchi; Reddy B. S. N (Wolters Kluwer Medknow Publications, 2004)
Androgenetic alopecia (AGA) is one of the most common causes of hair loss in genetically predisposed men and women. We studied the therapeutic efficacy and safety of oral finasteride in male patients with AGA. A total of 40 male AGA patients, 18-35 years of age, wad enrolled in the study for a period of 9 months. Oral finasteride, 1mg/day, was started and the drug efficacy was assessed on the basis of pre- and post-treatment clinical photographs, trichogram, hair pull test and self assessment of hair re-growth by the investigators. Routine hematological and bio-chemical investigations and a questionnaire related to sexual disturbances were carried out to assess the safety profile of the drug at each follow-up visit every three months. Improvement in hair growth was observed by comparing the paired pre- and post-treatment global photographs (p<0.05), decreased hair shedding by the patientsâ€ self assessment (p<0.05), hair pull test evaluation (p<0.001) and increase in anagen-telogen hair ratio (p<0.001) with the trichogram, as early as 3 months of finasteride therapy with maximum benefit in the mid-area followed by vertex and frontal areas. No significant side effect related to the drug was observed. It is concluded that oral finasteride is a relatively safe, well tolerated and efficacious drug for AGA in Males.